2015
DOI: 10.3892/ol.2015.3016
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin-2 receptor polymorphism predicts lymph node metastasis in colorectal cancer patients

Abstract: Abstract.To analyze the single nucleotide polymorphisms (SNPs) of two subtypes of neurokinin (NK) receptors, NK1R and NK2R (also known as TAC1R and TAC2R), in colorectal cancer (CRC), peripheral blood samples were collected from 199 CRC patients. Direct-sequencing was performed to identify the NK1R rs10198644 and NK2R rs4644560 SNPs. Genotype results were correlated with clinical factors. The allele frequencies of NK1R rs10198644 GC, CC and GG were 52, 17 and 31%, respectively, while that of NK2R rs4644560 GC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…In midgut carcinoid tumors, patients with persistent plasma NKA levels had significantly worse survival than patients with stabilized or downregulated plasma NKA levels 44 . Moreover, a previous paper indicated that NK2R gene polymorphisms predicted lymph node metastasis in CRC patients 45 . In our study, we found that NK2R was overexpressed in the tumor tissues of patients with CRC and high expression was associated with poor survival from the analysis based on TCGA public dataset 46,47 .…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In midgut carcinoid tumors, patients with persistent plasma NKA levels had significantly worse survival than patients with stabilized or downregulated plasma NKA levels 44 . Moreover, a previous paper indicated that NK2R gene polymorphisms predicted lymph node metastasis in CRC patients 45 . In our study, we found that NK2R was overexpressed in the tumor tissues of patients with CRC and high expression was associated with poor survival from the analysis based on TCGA public dataset 46,47 .…”
Section: Discussionsupporting
confidence: 51%
“… 44 Moreover, a previous paper indicated that NK2R gene polymorphisms predicted lymph node metastasis in CRC patients. 45 In our study, we found that NK2R was overexpressed in the tumor tissues of patients with CRC and high expression was associated with poor survival from the analysis based on TCGA public dataset. 46 , 47 Based on these findings, we speculate not only that NKA signaling through NK2R may be related to the development and malignancy of CRC, but also that NKA–NK2R expression levels may be useful biomarkers to evaluate the malignancy of colon cancers.…”
Section: Discussionmentioning
confidence: 59%
“…Via migration and invasion, one primary tumor could spread to several organs and form multiple metastases. Colorectal cancer, for example, may form liver metastasis [27], lung metastasis [28], bone metastasis [29] and lymph node metastasis [30]. It has been reported that ATAD2 is highly expressed in colorectal cancer, and it is associated with liver metastasis, lymph node metastasis and poor prognosis of colorectal cancer patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of tachykinin receptor coding genes was found in breast cancer, colon cancer, and other tumors. Nevertheless, the role of TACR2 in cancer progression remains unclear [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%